Low-head direct chill slab casting of aluminium alloy AA-6061: 3-D numerical study. (3rd May 2016) - Hasan, Mainul; Begum, Latifa
Abstract : An industrial-sized vertical low-head direct chill slab casting process for the aluminium alloy AA-6061 is modelled by taking into account the 3-D turbulent melt flow and heat transfer in the liquid sump and by giving proper consideration of the mushy region solidification aspect of the process. Computed results for the steady-state phase of the casting process are presented for four casting speeds, varying from 60 to 180 mm min −1, for three metal–mould effective heat transfer boundary conditions, varying from 1.0 to 4.0 kW m −2 K −1 and for three inlet melt superheats of 16, 32 and 64 ° C. A step-wise change of the cooling water temperature in the mould, impingement and free streaming regions are considered to reflect the actual operations. Detailed results in the form of velocity and temperature fields, solidification shell and mushy region thickness, sump depth and temperature profiles at four critical locations along the caster are provided and discussed.